Young chinese children's remote peer interactions and social competence development during the COVID-19 pandemic. (31st January 2022) - Luo, Wenwei; Berson, Ilene R.; Berson, Michael J.; Han, Sophia
Abstract: The COVID-19 pandemic has changed the way young children engage in peer communication. The aim of this study was to explore how young children engaged in peer interaction remotely by examining young children's multimodal interactions during the pandemic. Visual and audio data posted to Douyin (China's most popular live-streaming site) between January 23, 2020 and May 6, 2020 were collected and analyzed. Mediated discourse analysis was used to explore young children's remote interactions as captured on video recordings. Results support the critical role of play materials and tangible tools in mediating young children's peer interactions and participation in remote environments.